Expression of osteoclastogenic and anti-osteoclastogenic cytokines differs in mouse gingiva injected with lipopolysaccharide, peptidoglycan, or both. (February 2021) - Ozaki, Yukio; Kishimoto, Takaaki; Yamashita, Yasunori; Kaneko, Takashi; Higuchi, Kanako; Mae, Megumi; Oohira, Masayuki; Mohammad, Alam Ibtehaz; Yanagiguchi, Kajiro; Yoshimura, Atsutoshi
Highlights: LPS and PGN induced alveolar bone resorption to different degrees. LPS-injection mostly induced TNF-α and IL-10 expression in mouse gingiva. PGN-injection mostly induced IL-17 expression in mouse gingiva. TNF-α, IL-10 and IL-17 differentially regulated in vitro osteoclastogenesis. Abstract: Objective: Bacterial substances in subgingival biofilm evoke alveolar bone resorption. We previously reported that gingival injection of bacterial lipopolysaccharide (LPS) and peptidoglycan (PGN) induced alveolar bone resorption in mice. However, the mechanism by which LPS and PGN induce osteoclast formation has not been investigated. The aim of this study is to clarify the role of osteoclastogenic and anti-osteoclastogenic cytokines in the alveolar bone resorption induced by LPS and PGN. Materials: LPS from Escherichia coli, PGN from Staphylococcus aureus, or both were injected into the gingiva of mice every 48 h for a total of 13 times. Alveolar bone resorption was assessed histochemically by tartrate-resistant acid phosphatase staining. Expression of the receptor activator of nuclear factor-κB ligand (RANKL), tumor necrosis factor (TNF)-α, interleukin (IL)-17, and IL-10 were analyzed by immunostaining. To analyze the role of these cytokines, RANKL-pretreated mouse bone marrow macrophages were stimulated with LPS, PGN, or LPS + PGN with or without anti-TNF-α antibody, IL-17, or IL-10. Results: Alveolar bone resorption was induced by both LPS and PGN and exacerbated by LPS + PGN. LPS induced higher RANKL expression than PGN. Expression of TNF-α and IL-10 was correlated with bone resorption. PGN injections induced the strongest expression of IL-17, followed by LPS + PGN and LPS. In an in vitro osteoclastogenesis assay, anti-TNF-α antibody and IL-10 inhibited osteoclast formation, but IL-17 promoted it. Conclusion: LPS, PGN, or LPS + PGN injections induce distinctive expression of TNF-α, IL-10, and IL-17, suggesting that the composition of these bacterial ligands in dental plaque is critical for alveolar bone resorption.